(untitled) (Journal of Psychiatrists’ Association of Nepal, 2020)
Introduction: First Methadone Maintenance Programme (MMTP) in Nepal was started in the year 1994. This study was done to study and explore/compare findings of the present study with that of studies published in Nepal in the new millennium. Material and Method: Study was conducted at the Mental Hospital, Lalitpur, Kathmandu, Nepal from 1994 to 2002. Data was collected for the initial 5 years from 1994 to 1998. These patients were followed up for the next five years till 2002. Data thus obtained are presented in a tabulated form, in terms of frequencies and percentages. Results: A total of 204 patients were put on Methadone Maintenance Treatment Programme (MMTP) during the scheduled period. One-hundred-and-twenty-two (60%) of them were abusing buprenorphine. Severity of buprenorphine abuse was between 1-6 ampoules (2 ml per ampoule) per day. Approximately 40% (81) of them were sharing the injecting equipment. Seventy-seven (38%) of them had been in police custody in the past, for various reasons like theft, cheating, possessing, trafficking, violence and other antisocial behaviours. Forty-five percent (92) clients were retained at the end of 5 years. Sixty-nine family members (spouses, mothers, brothers) from these 92 regular methadone clients were interviewed. Eighty-six percent (79) of the interviewed family members reported significant improvement in clients’ health. Eighty-one percent (75) of the family members reported significant improvement among the methadone users’ family in financial responsibilities and interest in work. Overall, MMTP was found to have reduced the amount of illicit drug abuse significantly in these patients. These results are compared with the data of the subsequent published data on MMTP from Nepal in the new millennium. Conclusion: Though the present study data may appear to be of historical value, we are presenting these data, in the light of the findings of the newer studies published of late from Nepal. Till date, our study remained the largest MMT Programme in Nepal, in terms of number of patients studied, number of years of study and number of years of follow up of these patients.